Drugs addiction (Journal of the College of Education for Women, 2019)
The growing phenomenon of drug abuse in light of the increasing psychological and social pressures experienced by members of the community of wars and crises of the Iraqi society in the middle of the last decade was Andv societies that are free of the phenomenon of drug addiction, but with a high level events, wars and economic crises and the deterioration of the situation security and lack of control on the border with the neighboring countries, it has become a breeding ground and the focus of drug-smuggling gangs, all of which led to the spread of drug abuse, especially among the youth category, and undoubtedly the seriousness of drug abuse Taatmd negative community impacts, Valmtaati drug becomes a member unproductive and unable to earn his living as an acceptable level of society could threaten the corruption and crime, the community in which it frequently Almtaaton drug down the level of 9production and the weakening economy has marred disintegration becomes the scene of the problems and difficulties generated by people Almtaaton drugs